2023
DOI: 10.1186/s12902-022-01261-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the efficacy of thyroglobulin and thyroglobulin/ thyroid-stimulating hormone ratio models in predicting a successful response to radioactive iodine therapy

Abstract: Background The thyroglobulin (Tg)/ thyroid-stimulating hormone (TSH) ratio has manifested to be a reliable marker for predicting prognosis in patients with differentiated thyroid carcinoma (DTC). The objective of this study was to compare the efficacy of Tg and Tg/TSH ratio models in predicting a successful response to radioactive iodine therapy. Methods One thousand six hundred forty-two DTC patients receiving 131I radiotherapy were finally enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…It con rms and expands the conclusions of Ju et al who compared models including Tg and Tg/TSH showing that both Tg and Tg/TSH rations could be considered predictors of the effects of RAI. However, in their study, the prediction model including Tg performed even better than model including Tg/TSH [29] The cut-off for Tg concentration to predict a persistent disease suggested in previous studies varied from 0.27 to 30 mg/l. In a meta-analysis by Webb et al [50], which included 15 studies involving 3900 patients, a cut-off of 10 mg/L was determined, demonstrating a good negative predictive value (NPV).…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…It con rms and expands the conclusions of Ju et al who compared models including Tg and Tg/TSH showing that both Tg and Tg/TSH rations could be considered predictors of the effects of RAI. However, in their study, the prediction model including Tg performed even better than model including Tg/TSH [29] The cut-off for Tg concentration to predict a persistent disease suggested in previous studies varied from 0.27 to 30 mg/l. In a meta-analysis by Webb et al [50], which included 15 studies involving 3900 patients, a cut-off of 10 mg/L was determined, demonstrating a good negative predictive value (NPV).…”
Section: Discussionmentioning
confidence: 71%
“…Due to the potential stimulation of Tg production by TSH, Tg concentrations in pre-RAI therapy patients may be in uenced by their TSH levels [29]. Consequently, extensive research has been conducted on the correlation between the Tg/TSH ratio and the outcomes of initial RAI therapy [27,30,45].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies pointed out that the recurrence rate of patients with ER was only 1-4% [5]. In addition, a series of studies demonstrated that the stimulated thyroglobulin (sTg), which is obtained as early as a few weeks after surgery is correlated to the recurrence and development of cancer [6][7][8][9]. However, the relationship between sTg and the therapeutic response to RAI is still unknown.…”
Section: Introductionmentioning
confidence: 99%